Agriculture communication in Malaysia: the current situation - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham; Ramli, Nor Sabila (Science Publications, 2010)
Problem statement: Without doubt, it is important to expose and educate farmers with the current and updated agriculture information. To implement this, the related agriculture agencies in Malaysia should consider the best channels for them in spreading the needed valuable agriculture information to the farmers. The question that can be raised now, can the mass media be the right channel for agriculture information dissemination and is the mass media has been utilized in disseminating the agriculture information to the farmers. Approach: This is a conceptual study discussing the usage of mass media in disseminating agriculture information. The data of this study are gained through literature analysis and document analysis. The data is presented descriptively. Results: Based on the analyses done, it was found that majority of Malaysian nowadays can afford to own their own mass media such as television, radio and internet. The number of available television channels, radio channels and newspapers either free or paid are encouraging. Currently, there are three television agriculture programs aired on RTM, while currently there are five agriculture radio programs aired on local radio stations, one program aired on Klasik National FM and the other four programs aired on four different states FM. For newspapers, there are two daily newspapers that provide agriculture information to their readers namely Utusan Malaysia and Berita Harian. Based on the data gained, usage of internet especially on website surfing must be encouraged among the farmers. Mobile web system initiated by five agriculture agencies in Malaysia is seen as a wise step for information dissemination and information sharing. Conclusion: Even though mass media in Malaysia has played its' role in disseminating agriculture information, the number of programs and spaces produced and provided can be doubled, hence it is recommended that local giant agriculture based companies can play their role in providing more fund or sponsorship in producing more agriculture programs for the farmers.